Experimental studies on thread-fixed one-side bolted connection of beam to hollow square steel tube under static bending moment. (1st July 2020) - Wang, Peijun; Sun, Lele; Liu, Mei; Zhang, Boxun; Hu, Xianfeng; Yu, Jianxin
Highlights: Tests on TOBC to HSST column under static load were presented. Different strengthening methods to TOBC were proposed and tested. Bending moment capacity of TOBC could be increased by strengthening measures. Design methods for calculating yield bending moment of TOBC were proposed. Abstract: Test results on the T hread-fixed O ne-side B olted C onnection (TOBC) of a beam to a H ollow S quare S teel T ube (HSST) under static bending moment were presented and corresponding design methods were proposed. In order to enhance the initial stiffness and bending moment capacity of the TOBC, different strengthening methods to the connection, including backing plate and H-shaped stiffener, were investigated. Four TOBCs were tested under monotonic loading and a traditional N ut-fixed D ouble-sides B olted C onnection (NDBC) was tested for comparison. Failure modes, bending moment-rotation curves, and strain evolution curves measured from tests were presented. Test results indicated that the yielding bending moment, the ultimate bending moment and the ultimate rotation of a TOBC strengthened with backing plate were only a little lower than those of a NDBC, but the initial stiffness was improved. The yielding bending moment, the ultimate bending moment and the initial stiffness of a TOBC strengthened with H-shaped stiffener were higher than those of a NDBC, but the ultimate rotation decreased. All TOBCs tested met the seismic ductility requirement of not less than 30 mrad, suggested by the US seismic code FEMA-350. Based on the experimental results, design methods for calculating the bending moment capacity of TOBCs under failure modes of the hole threads failure, the endplate yielding and the column wall yielding were proposed, respectively. The calculated yielding bending moment capacity of a TOBC agreed well with the test result.